BEDSIDE ULTRASOUND IN CARDIAC EMERGENCY - Mustahsan, Syed Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Dear Sir, The cardiovascular disorders are the leading cause of death all over the world. Of them, cardiogenic shock is the major cause in Pakistan.1 The increasing number of cardiac emergencies requires prompt diagnosis and treatment. The use of ultrasound is clinically implicated over the last 50 years as a first-line test for the cardiac evaluation of symptomatic patients.2 The clinical utility of ultrasound is widespread in the valuable assessment and timely diagnosis of cardiac ill patients. It is easy to handle and has a good imaging quality to be used in emergency settings and it has relatively low cost. It is safe and can be repeated at any time to detect changes in patient hemodynamics.3 A cardiac ultrasound can be used to evaluate the motion of heart, its structure, to detect any valve dysfunction, evaluate heart murmurs, determine any fluid collection around the heart and to visualize the blood flow to heart for detection of any atherosclerosis, so the ultrasound can be used in different ways to detect the anomalies of the heart. Future research remains to be carried out to determine the efficacy of bedside ultrasonography.4 By using a pocket-sized ultrasound in cardiac emergencies, correct diagnosis can be achieved in almost 1 of 5 patients which can result proper treatment strategy.5 Even rapid cardiac sonography can be successfully integrated in the ACLS response.6 Equally important to the technical performance of this modality is the training of the clinicians who use it. Even before images are acquired, physicians who perform it need to be knowledgeable about the appropriate use of this technique.7 I request the health authorities to conduct sessions and training programs for the medical professionals regarding bedside cardiac ultrasound and make it a criterion which can improve our emergency situations and to provide accurate treatment. All efforts have to be made to implement it successfully in our hospital settings to ensure the standard care given to the patients.